Opstanding : orgaan der Vlaamsche Clarté-groepen (Ukkel: A. Daenens; Brussel: Clarté)
"Verschijnt ten minste eenmaal in de maandRedactie: H. Barbusse, A. Van Hoogenbempt, P. Kenis, P. Colin, O. Volkart, J.L.A. Peremans, D. Boens, J. Boor, P. Van OstayenBeheer/Administratie: Koolenstraat 12, Brussel / Sint-Kathelijnestraat 26, BrusselDrukker/Drukkerij: Vanderkelen, James Wattstraat 25, Schaarbeek-Brussel / Jaak Vandoren, Leuven"